Socio-Economic Risk Assessment and Peril Analysis in the Context of the COVID-19 Pandemic and Emergencies - Novikova, Olga; Khandii, Olena; Shamileva, Larisa (European Journal of Sustainable Development, 2021)
The article proposes a methodology for assessing socio-economic risks and analysing perils in the context of the COVID-19 pandemic and emergencies, and presents the results of its testing. The methodology allows assessing changes in labour risks by possible values of internal indicators. This makes it possible to develop scenario approaches in case of a change in quarantine restrictions or their lifting. Testing of the developed methodology for assessing socio-economic risks and analysing perils caused by the impact of the COVID-19 pandemic on the domestic labour market and employment is based on determining changes in economic conditions of risk emergence and occurrence, direct employment risks, and assessment of socio-economic consequences of risks in case of strict quarantine measures during the 2nd quarter of 2020. A feature of the proposed scientific and methodological support for assessing socio-economic risks and analysing perils in the context of the COVID-19 pandemic is taking into account the basic principles of the European system of social indicators using quantitative methods of assessing social risks in the workplace. The practical significance of the obtained results is that the introduction of the developed scientific and methodological support, and practical recommendations will promote the development of preventive measures to deal with socio-economic risks and perils in the domestic labor market and employment, to improve social protection during the COVID-19 pandemic, and to prioritise the government measures based on the risk ranking according to the occurrence, and the impact probability.